ANTIBIOTIC SUSCEPTIBILITY OF ENTEROBACTERIACEAE ISOLATED FROM DOMESTIC WATER TANKS IN BIDA, NIGER STATE, NIGERIA - , R. G, MUHAMMAD; .I. L, MUHAMMAD; . A, HAMZAT; A. R, SANI; .A, GIMBA (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2021)
Most communities (rural and sub urban) in Nigeria get their water supply from untreated sources like wells, streams, rivers and ponds that are mostly contaminated with pathogenic bacteria. This exposes people to gastroenteritis such as Typhoid fever, dysentery, diarrhea and cholera. Antibiotic Susceptibility of Enterobacteriaceae isolated from domestic water tanks in Bida town to some antibiotics was investigated. A total of forty (40) water samples were collected from different domestic water tanks located in the four (4) cardinal points of Bida town and subjected to physicochemical and bacteriological analysis. The bacterial isolates identified were further subjected to antibiotic susceptibility test using Septrin, Streptomycin, Chloramphenicol, Sparfloxacin, Ciprofloxacin, Amoxicillin, Augmentin, Gentamycin, Perfloxacin and Tarivid. The temperature and pH of the water samples favored the growth of Enterobacteriaceae. Conductivity, Biochemical oxygen demand (BOD), Chemical oxygen demand (COD), Total suspended solid, Total dissolved solid, Calcium, Zinc, Magnesium, and Nitrate of water samples were all above the WHO acceptable limit for drinking water. The result revealed that the total viable count of bacteria ranged from 1.0×104 cfu/ml to 9.9×104 cfu/ml in Eyagi and Banyagi (west) and GRA (South) respectively. Bacteria species isolated from the water samples included Escherichia coli, Salmonella sp, Enterobacter, Klebsiella, Pseudomonas, and Proteus. The most frequently isolated bacteria were Escherichia coli and Salmonella sp. with percentage frequency of 27.77% while the least isolated bacterium was proteus sp (4.16%). The percentage susceptibility pattern of the bacteria was: E. coli (30%), Salmonella sp. (20%), Enterobacter sp. (10%), Klebsiella sp. (20%), Pseudomonas sp. (20%), while Proteus sp, was 100% resistant to all antibiotics. The result of this findings is an indication that water stored in domestic tanks in Bida town is contaminated with different species of Enterobacteriaceae hence not safe for human consumption.